2014
DOI: 10.3892/ijmm.2014.1642
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoplasmic reticulum stress in apoptosis of differentiated mouse podocytes induced by high glucose

Abstract: Podocytes are terminally differentiated epithelial cells lacking the ability to proliferate. The loss of podocytes is a hallmark of progressive kidney diseases, including diabetic nephropathy (DN). Endoplasmic reticulum stress (ERS)-induced apoptosis is involved in a number of pathological conditions, including DN. The aim of the present study was to investigate whether a high glucose environment induces the apoptosis of podocytes through ERS. Differentiated mouse podocytes were divided into three groups: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 30 publications
1
64
0
Order By: Relevance
“…Our results were similar to other investigators. 7,43 Inagi et al 44 demonstrated that podocytes treated with hyperglycemia did not upregulate ER stress markers. As mentioned in the section of methods in their study, podocytes were cultured in the presence of 4.5 mg/ml (25 mM) D-or L-glucose for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to other investigators. 7,43 Inagi et al 44 demonstrated that podocytes treated with hyperglycemia did not upregulate ER stress markers. As mentioned in the section of methods in their study, podocytes were cultured in the presence of 4.5 mg/ml (25 mM) D-or L-glucose for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, long-term high blood sugar can weaken the synthesis of islet cells and secretion of insulin, and reduce insulin secretion or loss of glucose. On the other hand, long-term high blood sugar decreases the number of islet cells and increases failure islet beta-cell function in patients with diabetes [5][6][7]. STZ-induced diabetic rat model is similar to human diabetes, which has the same pathological and physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of apoptosis was closely associated with ERS. New evidence demonstrated that hyperglycemia induced apoptosis by activating ERS (67,68). In addition, in diabetic heart tissue, the ER was found to be swollen and dilated following ultrastructural analysis, suggesting abnormalities in the ER in a hyperglycemic environment (69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%